Replication and Transcription Activation by Polyomavirus Enhancer Motifs PEA1, PEA2, and PEA3 - McWilliams, H. M. (My University, 1991)
The polyomavirus enhancer is organized into three elements. One of these elements, Element 2, is particularly interesting because the activities of the factors which interact with it are highly regulated. There are at least three cellular proteins, PEA1, PEA2, and PEA3, which bind to adjacent sites in Element 2. These proteins are differentially active in mouse cells at different developmental stages and their activity is modulated by serum, tumor promoting agents and the products of several oncogenes. It is likely, therefore, that these cellular proteins play an important role in interpreting growth stimuli and other physiological cues in the mouse. A plasmid was contructed which can be used to test enhancer elements for their ability to activate both transcription and DNA replication. This plasmid includes the Py origin of replication and a minimal promoter, consisting of a TATA box only, controlling expression of a reporter gene. The activity of the PEA factors was studied by cloning the binding sites for these factors into this reporter plasmid as monomers, multiple tandem copies, and in paired combinations, and testing their ability to activate transcription and DNA replication in vivo. The results of these studies show that PEA1 and PEA3 can function independently and cooperatively to activate both replication and transcription. By contrast, PEA2 is unable to independently activate transcription and represses PEA1-activated transcription when the binding sites for these factors are located adjacent to one another. However, PEA2 functions cooperatively with PEA1 to activate DNA replication, and can weakly activate replication on its own.
Replication and Transcription Activation by Polyomavirus Enhancer Motifs
This thesis is missing page 157, the other copies of the thesis did not have the page either. -Digitization Centr
Keywords: replication; transcription activation; polyomavirus; polyomavirus enhancer motif; PEA1; PEA2; PEA3